The emergent firm : - Kay, Neil M. (Macmillan, 1984)
This book introduce the problem, entrepreneurial salome, more salome. Industrial organisation and boundes rationality, multinational enterprise, public policy nad bounded rationality, sysnthesis and antithesis, ingredients and recipes.